A critical review on ammonium recovery from wastewater for sustainable wastewater management. (November 2018) - Ye, Yuanyao; Ngo, Huu Hao; Guo, Wenshan; Liu, Yiwen; Chang, Soon Woong; Nguyen, Dinh Duc; Liang, Heng; Wang, Jie
Graphical abstract: Highlights: Growing global population ultimately calls for ammonium recovery. Wastewater is considered as the renewable resource for the ammonium recovery. The bioelectrochemical system can efficiently and effectively recover ammonium. Mechanism and technology of ammonium recovery were summarized. Abstract: The growing global population's demand for ammonium has triggered an increase in its supply, given that ammonium plays a crucial role in fertilizer production for the purpose of food security. Currently, ammonia used in fertilizer production is put through what is known as the industrial Haber Bosch process, but this approach is substantially expensive and requires much energy. For this reason, looking for effective methods to recover ammonium is important for environmental sustainability. One of the greatest opportunities for ammonium recovery occurs in wastewater treatment plants due to wastewater containing a large quantity of ammonium ions. The comprehensively and critically review studies on ammonium recovery conducted, have the potential to be applied in current wastewater treatment operations. Technologies and their ammonium recovery mechanisms are included in this review. Furthermore the economic feasibility of such processes is analysed. Possible future directions for ammonium recovery from wastewater are suggested.